Friction behaviors of elastic materials sliding on textured glass surfaces - Fujita, Naoki; Yamaguchi, Hajime; Kinoshita, Takumi; Iwao, Masaru; Nakanishi, Yoshitaka (Tribology international, 2022)
The friction behaviors of elastomer, polyacetal, and hard-felt writing tips sliding on various textured glass surfaces prepared via micro-slurry-jet technology were investigated via reciprocating friction tests. The friction coefficients of each writing tip could be varied using textured glass surfaces. Adhesive, abrasive, and deformation frictions were observed owing to two types of surface roughness (sub-millimeter-millimeter sized texture and nanometer sized fine roughness). By inducing a surface texture with a smaller pitch (sub-millimeter-millimeter sized texture) than the contact area of the writing tip, the largest changes of friction coefficients were observed for the elastomer. These reductions occurred due to reduced adhesive friction by decreasing real contact areas. •Friction behaviors of three commercial pen tips on textured glass measured.•Changes in the friction behaviors via reciprocating friction tests observed.•Friction coefficient reduced largest for elastomer due to reduced adhesive friction.